PENINGKATAN AKTIVITAS DAN HASIL BELAJAR SISWA MENGGUNAKAN MODEL PEMBELAJARAN KOOPERATIF TIPE JIGSAW PADA MATA PELAJARAN MATEMATIKA SISWA KELAS VII SMPN 2 BUMIRATU NUBAN TAHUN PELAJARAN 2014/2015 - Nur Basuki (UNIVERSITAS MUHAMMADIYAH METRO, 2015)
Based on preliminary observations obtained activity data and student learning outcomes are still low, especially subjects of mathematics, as many as 6 students or 28.23% of the students completed and 15 students or 71.78% of students have not been completed. Based on the above facts applied learning model of Jigsaw Cooperative type that aims to improve the activity and student learning outcomes in mathematics in comparison material and scale. The study involved 21 students of class VII SMPN 2 BUMIRATU Nuban in semester 1 Academic Year 2014 / 2015.This research used a Class Action Research (PTK) by using two cycles. Each cycle consists of four stages: planning, implementation, observation and reflection. Data collected by the observation sheet and test student learning outcomes in each cycle. From the analysis of the data shows that the use of cooperative learning model Jigsaw Type in the learning process of Mathematics students can increase the activity and student learning outcomes. It can be seen from the average percentage of the activity of students in the first cycle was 55.5 and increased in the second cycle to 70.5. While the average value of student learning outcomes in the first cycle was 58.75 and increased in the second cycle into 72.50